Effect of carbonization on the processing characteristics of rubber seed shell - L.O. Ekebafe; J.E. Imanah; F.E. Okieimen (Arabian Journal of Chemistry, 2017)
The effect of carbonization on the processing characteristics of rubber seed shell powder was studied. Rubber seed shells were carbonized at different temperatures and then ground into fine powder. The various powders obtained were then characterized by pH, bulk density, moisture content, iodine adsorption value, yield%, conductivity and loss on ignition. The results show that there was a significant change in the pH as the heating temperature increases. The bulk density and moisture content decrease with increasing heating temperature while the iodine adsorption number and the loss on ignition increase with increasing heating temperature thus showing that carbonization has a significant influence on the processing characteristics of rubber seed shell.